2020
DOI: 10.4103/ijo.ijo_1187_19
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multicolor imaging signatures of central serous chorioretinopathy lesions vis-a-vis conventional color fundus photographs

Abstract: Purpose: The current study compares the ability of multicolor imaging (MCI) to detect the lesions of central serous chorioretinopathy against conventional color fundus photographs (CFP). Methods: It was a retrospective, observational case series of 93 eyes of 58 patients of central serous chorioretinopathy who underwent MCI and CFP. MCI and spectral-domain optical coherence tomography (SD-OCT) were performed using Spectralis SD-OCT system (HRA + OCT). CFP was obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…MC image compiles the three reflectances into a pseudocolor image (Tan et al, 2016 ). Nowadays, several studies have identified the obvious value of MC images in posterior segment pathology diseases, such as central serous chorioretinopathy (CSC; He et al, 2020 ; Saurabh et al, 2020 ), epiretinal membranes (ERM; Song et al, 2019 ; Terasaki et al, 2020 ), diabetic retinopathy (DR; Roy et al, 2019 ; Arrigo et al, 2021 ), and age-related macular degeneration (AMD; Graham et al, 2018 ; De Rosa et al, 2020 ). On MC and GR images rather than CFPs, hard exudates, cotton-wool spots, retinal microaneurysms, and hemorrhages were better identified (Roy et al, 2019 ; Arrigo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MC image compiles the three reflectances into a pseudocolor image (Tan et al, 2016 ). Nowadays, several studies have identified the obvious value of MC images in posterior segment pathology diseases, such as central serous chorioretinopathy (CSC; He et al, 2020 ; Saurabh et al, 2020 ), epiretinal membranes (ERM; Song et al, 2019 ; Terasaki et al, 2020 ), diabetic retinopathy (DR; Roy et al, 2019 ; Arrigo et al, 2021 ), and age-related macular degeneration (AMD; Graham et al, 2018 ; De Rosa et al, 2020 ). On MC and GR images rather than CFPs, hard exudates, cotton-wool spots, retinal microaneurysms, and hemorrhages were better identified (Roy et al, 2019 ; Arrigo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al 21 compared the two image modalities in patients with polypoidal choroidal vasculopathy, concluding that, despite differences in the appearance, they are comparable in the detection of multiple features of the disease. Saurabh et al 22 compared the ability of MFI to detect a typical lesion of central serous chorioretinopathy against CFP, concluding that MFI had higher sensitivity and lower specificity for retinal pigment epithelium atrophy, that serous pigment epithelium detachment was more easily detected on MFI, and that both image modalities were similar in their ability to detect subretinal fluid. Regarding the presence of fibrin, it was seen more distinctly on CFP.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution, detailed MCI can highlight structures and pathologies not visible on ophthalmoscopy and color fundus photographs (CFP) in lesions of epiretinal membrane, 12 , 13 diabetic macular edema, 14 and central serous chorioretinopathy. 15 …”
Section: Discussionmentioning
confidence: 99%